Conceptual framework of viral marketing: a review of the literature of the last years: Marco conceptual del marketing viral: una revisión de la literatura de los últimos años - Garcia-Salirrosas, Elizabeth Emperatriz (2020)
The purpose of this research was to build a conceptual framework of viral marketing startingfrom a literary review of the various studies published in indexed magazines in the recentyears. It is concluded that viral marketing can be defined as a marketing technique thatuses the intercommunication of consumers through the 2.0 tools, managing to spread themessage on the network at initiative of the user, giving the possibility to increase the valueof the organization through fast and unlimited transmission, similar to a flu or computervirus. This technique takes advantage of people’s communication, since feelings, emotionsand experiences are transmitted through their networks. Viral marketing must be usedconveniently, justifying its use through a simple message that goes beyond repeatinginformation in the different media, thus achieving a good communication practice, andcreating interconnectivity between organizations and their consumers.